If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 8(x + 1) = 6x Reorder the terms: 2 + 8(1 + x) = 6x 2 + (1 * 8 + x * 8) = 6x 2 + (8 + 8x) = 6x Combine like terms: 2 + 8 = 10 10 + 8x = 6x Solving 10 + 8x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 8x + -6x = 6x + -6x Combine like terms: 8x + -6x = 2x 10 + 2x = 6x + -6x Combine like terms: 6x + -6x = 0 10 + 2x = 0 Add '-10' to each side of the equation. 10 + -10 + 2x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = 0 + -10 2x = 0 + -10 Combine like terms: 0 + -10 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| -30=6c-18 | | h=-16t^2+6 | | 15/a=30/98 | | 6x+5+x=4+2x-4 | | 53/2=18/x | | -14x=6 | | 12y+2=234 | | 2m^2-5=39 | | (8x+9y)(8x+9y)-(8x-9y)(8x-9y)= | | 5/6=n/42 | | 7.5x-5.7y+8.8=0 | | -8-5x=-17 | | 7y-6y+2=-9 | | 3/4M=46.50 | | 10b-2=2 | | 3/5+3 | | (3xy+2)(5xy-3)= | | 6.28/7.07 | | 4c-12=-3 | | (7x^2y-2xy-5)+(-5x^2y+5xy-10)= | | 7.07/6.28 | | 11-7*3=x | | 3/5(3)+3 | | 12b-2(b-1)=6-4b | | 5x^2-2x= | | 5/x-8 | | 4x^2+4x+1=25 | | -7*0-9y=63 | | (6-y^9)(6+y^9)= | | -7+4y+4y^2=0 | | w/7=28 | | 4a-8*(a-2)=0 |